2018
DOI: 10.1016/j.hrtlng.2018.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of music intervention on inflammatory markers in critically ill and post-operative patients: A systematic review of the literature

Abstract: Music intervention may decrease cortisol levels, but other biomarkers remain unchanged. Given the low level of evidence, further research on music effects on inflammatory biomarkers is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 28 publications
1
27
0
7
Order By: Relevance
“…A Cochrane Review of music interventions with mechanically ventilated patients indicated that only 1 of the 14 studies reviewed included a board certified music therapist as a member of the research team [22]. As a result, in many studies the music was selected by the researchers and provided patients only limited options of music to listen to throughout the course of the study [50][51][52][53]. While researchers may refer to this as patient-preferred music, in essence patients are choosing what music to listen to, based on a pre-determined and a restrictive list of music, thus choosing what to listen to from limited options.…”
Section: Classicalmentioning
confidence: 99%
See 1 more Smart Citation
“…A Cochrane Review of music interventions with mechanically ventilated patients indicated that only 1 of the 14 studies reviewed included a board certified music therapist as a member of the research team [22]. As a result, in many studies the music was selected by the researchers and provided patients only limited options of music to listen to throughout the course of the study [50][51][52][53]. While researchers may refer to this as patient-preferred music, in essence patients are choosing what music to listen to, based on a pre-determined and a restrictive list of music, thus choosing what to listen to from limited options.…”
Section: Classicalmentioning
confidence: 99%
“…Music that is 60-80 beats per minute (BPM) is ideal for fostering this relaxation response. Music that is preferred by the listener is more effective in fostering relaxation[21,28,[49][50][51][52].…”
mentioning
confidence: 99%
“…Nach vorliegenden Berichten und kürzlich publizierten prospektiv-randomisierten Studien ist ein positiver Effekt von Musik in vielen Fachdisziplinen der Medizin und auch in der Intensivmedizin beobachtet worden [4,15]. Auch bei postoperativen Patienten, ob aus der Viszeralchirurgie, der Herzchirurgie, der Orthopädie und der Frauenheilkunde, um exemplarisch nur einige zu nennen, wurden positive Wirkungen von Musik bei kritisch Kranken hinsichtlich der Parameter Schmerz, Stress und Angst nachgewiesen [17,25]. Trotz vorliegender randomisierter Studien bleiben im klinischen Alltag noch viele Fragen offen.…”
Section: Schlussfolgerungenunclassified
“…For example, studies show that serum concentrations of both salivary IgA, a marker of immune function, and oxytocin, a hormone involved in human connection, increase after singing lessons [14,15]. Several studies also report decreases in cortisol, a hormone integral to the stress response, for subjects during the act of singing and other creative activities [13,14,[16][17][18][19][20]. Group singing in particular has also been shown to reduce stress and arousal, measured by serum levels of ACTH, a precursor to cortisol [21].…”
Section: Introductionmentioning
confidence: 99%